The application of mind mapping in the standardized education of inpatient physicians in nephrology - Yao Hu; Yuanbin Xiang; Min Lei; Yuxi Wu; Min Sun (Scientific Reports)
Abstract This study aims to investigate the effectiveness of mind mapping in the standardized training and education of internal medicine resident physicians in nephrology. Sixty trainees undergoing rotations in the Nephrology Department at Chengdu University Affiliated Hospital between January 2021 and December 2023 were randomly assigned to control and observation groups, each comprising 30 trainees. The observation group received mind mapping teaching, while the control group received traditional teaching methods. The clinical thinking training of the two groups was then compared. The observation group outperformed the control group in all aspects of the Mini-CEX assessment, including medical interviews, humanistic care, clinical judgment, communication skills, overall performance, and total score, with statistical significance (P < 0.05). However, there were no statistically significant differences between the two groups in the areas of physical examination and organizational effectiveness (P > 0.05). Furthermore, the observation group achieved higher scores than the control group in the final theory exam, skill exam results, and satisfaction, with statistically significant differences (P < 0.05). Mind mapping not only aids in the consolidation of fundamental memorized knowledge but also enhances clinical thinking skills, thereby playing a pivotal role in assisting resident physicians in establishing a comprehensive knowledge base in nephrology and improving the effectiveness of their training.